Smoldering type adult T‐cell leukemia/lymphoma effectively treated with mogamulizumab (anti‐CC chemokine receptor 4 monoclonal antibody)—A case report. Issue 5 (16th April 2019) - Nishikawa, Yotaro; Mochida, Kosuke; Kubo, Tamaki; Horikawa, Nagako; Nemoto, Rieko; Amano, Masahiro
Key Clinical Message: The use of mogamulizumab needs careful consideration because of severe adverse reactions such as graft‐vs‐host disease. However, refractory specific skin lesions of smoldering type adult T‐cell leukemia/lymphoma can be effectively treated with mogamulizumab when patients have no opportunity to receive hematopoietic stem cell transplantation like our case. Abstract : The use of mogamulizumab needs careful consideration because of severe adverse reactions such as graft‐vs‐host disease. However, refractory specific skin lesions of smoldering type adult T‐cell leukemia/lymphoma can be effectively treated with mogamulizumab when patients have no opportunity to receive hematopoietic stem cell transplantation like our case.